2022
DOI: 10.1002/ece3.9473
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial legacies influence plant survival and growth in mine reclamation

Abstract: Plants alter soil biological communities, generating ecosystem legacies that affect the performance of successive plants, influencing plant community assembly and successional trajectories. Yet, our understanding of how microbe‐mediated soil legacies influence plant establishment is limited for primary successional systems and forest ecosystems, particularly for ectomycorrhizal plants. In a two‐phase greenhouse experiment using primary successional mine reclamation materials with or without forest soil additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…For example, Hannula et al (2021) found that while bacterial communities quickly respond to alterations in plant community composition, microbially mediated soil legacy effects remain after five months of succession. Similarly, McMahen et al (2022) found that plant succession is highly influenced by mycorrhizal dependence, with ECM plant hosts demonstrating higher seedling survival and biomass in early succession. Additionally, other belowground root-colonizing fungi such as dark septate endophytes (DSE) can enhance aboveground plant growth through increased nitrogen (N) and phosphorus (P) root absorption as well as increased root surface area (He et al 2019;Xie et al 2021).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Hannula et al (2021) found that while bacterial communities quickly respond to alterations in plant community composition, microbially mediated soil legacy effects remain after five months of succession. Similarly, McMahen et al (2022) found that plant succession is highly influenced by mycorrhizal dependence, with ECM plant hosts demonstrating higher seedling survival and biomass in early succession. Additionally, other belowground root-colonizing fungi such as dark septate endophytes (DSE) can enhance aboveground plant growth through increased nitrogen (N) and phosphorus (P) root absorption as well as increased root surface area (He et al 2019;Xie et al 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, patterns of plant growth, reproduction, and competitive ability in current plant communities may be driven by soil-microbial changes induced by previous species no longer present or prevalent (Bever 2003, van der Putten et al 2013. Specifically, mutualistic ectomycorrhizal (ECM) fungi play an integral role in mediating the productivity and diversity of aboveground plant communities through facilitating shifts in nutrient availability as well as soil structure and stability across early, mid-, and late successional stages (Ka lucka & Jagodziński 2017;McMahen et al 2022;Zhao et al 2023Wang et al 2023. For example, Hannula et al (2021) found that while bacterial communities quickly respond to alterations in plant community composition, microbially mediated soil legacy effects remain after five months of succession.…”
Section: Introductionmentioning
confidence: 99%
“…Berkaitan dengan pentingnya peranan tanah pucuk dalam kegiatan reklamasi sesuai dengan penelitian yang dilakukan McMahen et al pada tahun 2022 yang menjelaskan bahwa penambahan volume kecil tanah pucuk yang ditargetkan dari ekosistem asli dapat meningkatkan kelangsungan hidup dan pertumbuhan bibit awal, mendorong pemulihan komunitas mikroba tanah yang terbatas, dan menjadi solusi yang menjanjikan untuk reklamasi tambang ketika ketersediaan tanah pucuk terbatas (McMahen et al, 2022).…”
Section: Hasil Dan Pembahasan Pelaksanaan Reklamasiunclassified
“…Soil is an important carrier of plants and is the basis of productive forestry [14]. Soil microorganisms play a critical role in regulating carbon (C) and nitrogen (N) pools and nutrient cycles by promoting the activities of terrestrial ecosystems [15][16][17]. The plant rhizosphere is a soil micro-area where plant roots and microorganisms communicate more actively [18].…”
Section: Introductionmentioning
confidence: 99%